Radicle Emergence Test of Various Sorghum Varieties (Sorghum bicolor (L.) Moench) Using the Between Paper and Top of Paper Germination Methods - Noviana Miming Dwi Wulansari; I Gede Wijana; Ida Ayu Putri Darmawati (Jurnal Penelitian Pendidikan IPA, 2026)
High reliance on rice and limited national production drive the need to develop sorghum as an alternative food crop. This development requires high-quality seed and rapid, reliable testing methods. This study evaluated the effect of germination methods on radicle emergence (RE), assessed varietal differences in RE rate, and examined the ability of the RE test to estimate germination percentage (GP). The experiment used a nested design with germination method as the main factor, between paper and top of paper, and five sorghum varieties nested within each method, namely Mandau, Super 1, Bioguma 1, Bioguma 2, and Bioguma 3, with four replications. Top of paper detected radicle emergence earlier than between paper, with the optimal observation time at 48 hours. Super 1 showed the highest RE and GP, followed by Bioguma 3, while Mandau and Bioguma 2 showed lower performance. Regression analysis between RE and GP produced the equation y = 1.038x − 3.32 with R² = 0.7474, indicating a strong positive relationship. These results demonstrate that RE observation at 48 hours provides a rapid and accurate indicator of sorghum seed viability and supports the selection of superior varieties for seed production